Criminological study of persons and typology committing crimes with a mercenary purpose - Shamistan oglu, Mansurov Vugar (Technium Social Sciences Journal, 2023)
One of the crimes that stand out with special weight in the structure of common crimes are crimes committed for mercenary motives. Criminological analysis of the personality of criminals with the motive of self-interest as an object of study requires the study of quantitative and qualitative indicators of crimes in this area. To create a clear picture of the personality of criminals with a motive for self-interest, it is necessary to investigate the personality of the criminal as a whole. Preliminary information about a person creates fertile ground for studying the criminal behavior of individuals who commit crimes with a motive for self-interest. Personality is considered one of the main means of understanding human behavior.